Protection of children's rights during implementation of guarantees in executive proceedings: theoretical and legal study - Stepanenko, Natalya; Kubrak, Danylo; Степаненко, Наталія В'ячеславівна (University of Warsaw, 2023)
The article delves into the theoretical and legal dimensions of safeguarding children’s rights within the framework of enforcement proceedings guarantees. It presents the guarantee system as comprising various elements, such as procedural oversight, appeals mechanisms against executor actions, measures for holding violators accountable, involvement of relevant professionals, and the normative regulation of rights and obligations for all participants. Through legislative analysis and practical examination, the article asserts that safeguarding children’s rights in enforcement proceedings unfolds in two primary facets: protection of property rights and protection of personal non-property rights. In the realm of property rights, emphasis is placed on securing child support payments from debtor parents to foster the child’s well-rounded development. Additionally, it addresses preventing the eviction of a minor from mortgaged housing in cases involving parents-mortgagors. For the protection of non-property rights, measures include child removal, establishment of visitation rights, and removal of obstacles to visitation. The article underscores the importance of sound reasoning and evidence when considering temporary child placement and ensures debtors receive copies of enforcement proceedings decisions during searches. It advocates for petitioning the court to amend or clarify visitation-related decisions. Special attention is given to the involvement of professionals such as doctors, teachers, and psychologists in enforcement proceedings to safeguard minors’ rights, ensuring their mental and physical well-being and preventing potential abuse by involved parties
Keywords: protection; child rights; enforcement proceedings; guarantees of enforcement proceedings